การวิเคราะห์ความสัมพันธ์ของการศึกษากับการเจริญเติบโตทางเศรษฐกิจ - สิริมา นาคสาย (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2020)
This paper is a study of the relationships between education and economic growth comparing Thailand, Vietnam, Republic of China, and Malaysia. The dependent variable is Gross Domestic Product (GDP) and independent variables are registrations of primary school, high school and higher education, and secondary data of academic expenditures in 2003 - 2017. The study uses econometric method, ARDL, to test a long-run relationship, and uses Error Correction Model to test a short-run adjusting to equilibrium. A cointegration result shows that; 1) Thailand’s higher education registration has equilibrium relationship with GDP, 2) Malaysia’s academic expenditure has long-run equilibrium relationship with GDP, 3) China’s registration of primary school and academic expenditure has long-run equilibrium relationship with GDP, and 4) Vietnam does not have long-run equilibrium relationship with any variable. The result of Error Correction Model shows that primary registration has short-run equilibrium relationship in 4 countries. High school registration has short-run equilibrium in Malaysia, China, and Vietnam. Higher education registration has short-run equilibrium in Vietnam. And academic expenditure has short-run equilibrium in Malaysia and Vietnam.